Improvement of vertigo symptoms after 2 months of Vertigoheel treatment: a case series in patients with bilateral vestibulopathy and functional dizziness - Ganeva, Dilyana; Tiemann, Rolf; Duller, Stephan; Strupp, Michael (Frontiers in Neurology, 2023)
Background Dizziness is a common leading symptom in bilateral vestibulopathy (BVP) and functional dizziness (FD), with significant negative effects on functional ability and quality of life. Vertigoheel is a widely used non-prescription drug for the treatment of vertigo. In order to generate systematic data for Vertigoheel in BVP and FD, we conducted a non-interventional study assessing vertigo symptoms. Methods This study was conducted as an open-label, prospective, monocentric, non-interventional case series (ClinicalTrials.gov identifier NCT05897853). Patients with BVP and FD received Vertigoheel according to market approval for an observational period of 2 months. Change from baseline after 2 months was assessed for the following endpoints: Dizziness Handicap Inventory (DHI) as the primary endpoint, quality of life (QoL) by EQ-5D-5L, and body sway by static posturography. Patients with FD were additionally assessed for depression and anxiety by PHQ-9 and GAD-7 questionnaires. Patients with BVP were assessed for vestibular function by video head impulse testing and caloric testing. Adverse events and other safety-related observations were evaluated. Results Of 41 patients with FD and 13 with BVP, two with FD and none with BVP dropped out before the follow-up visit. Both patient groups showed significantly improved disability caused by dizziness after 2 months: In BVP, the DHI decreased on average by 13.2 points from 45.4 to 32.2 (p < 0.001). In FD, the DHI decreased on average by 12.0 points from 46.5 to 34.5 (p < 0.001). In patients with FD, significant improvements were also observed for the secondary endpoints QoL, anxiety, and depression. No significant change was observed for posturography readouts. In patients with BVP, there were no statistically significant improvements for the secondary endpoints QoL, posturography, or vestibular function within the observation period. The study found no evidence of a safety risk. Conclusion The study provides evidence for Vertigoheel’s clinical safety and limited evidence – because of the non-interventional design – for its effectiveness in BVP and FD that are considered disease entities with high medical need for new treatment options. The results may serve as the basis for randomized placebo-controlled trials.